Análise de viabilidade econômica do uso de diversas fontes de biomassa para queima - Areias, Adriana Aparecida (Universidade Federal de São Carlos, 2020)
Biomass is a renewable resource that is increasingly being used as an energy source. This dissertation aimed to study the economic viability of using biomass for power generation. In Chapter 1, the contributions of renewable energy to sustainable energy production were studied. In addition, the types of solid biomass were addressed and what are the main parameters used to make their energy characterization. In Chapter 2, was studied the biomass market in the State of São Paulo and also the energy properties of the biomass analyzed: sugarcane bagasse, briquette, sawdust, firewood and eucalyptus forest, pine chips, charcoal and rice husks. In Chapter 3, an economical-energetic analysis was made on the following biomass destined for burning in the Sorocaba Metropolitan Region (RMS): briquette, sawdust, chips, firewood and eucalyptus forest and rice husk. In this chapter, the cost of energy, logistics, and price were analyzed. Finally, Chapter 4 gives a general conclusion of the work and also discusses the limitations and recommendations for future work. From the analysis of the results obtained in chapter 2, it was seen that there are more suppliers of firewood, wood chips and eucalyptus forest and the biggest demand for these biomasses are the sectors of food and beverages, furniture, red ceramics and paper and cellulose in the State of São Paulo. In relation to supply, the materials that have the highest production in this state are sugarcane bagasse, the eucalyptus forest and firewood and the pine forest. In the energy analysis, it was found that charcoal, wood, briquette, wood chips and eucalyptus wood and wood chips are more suitable for burning. In chapter 3, it was found that the biomasses that showed technical and economic feasibility to be used in the RMS were the chip and the eucalyptus log for several distance radii.
Economic viability analysis of the use of various sources of biomass for burning
Keywords: Bioenergia; Custo; Fornecedores; Energias Renováveis; Bioenergy; Cost; Suppliers; Renewable energy; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS